UNRAVELING THE SOCIAL SOLIDARITY OF RICE FARMERS: BETWEEN TRADITIONS AND MODERNIZATION CHALLENGES IN PAYA BIENG, BIREUEN - Sari, Mutia; Maliati, Nulwita; Fauzi, Fauzi; Husen, M. (FISIP Universitas Malikussaleh, 2025)
This study examines the social solidarity of rice farmers (study in Paya Bieng Village, Jangka District, Bireuen Regency). This study aims to find out the form of social solidarity of rice farmers and the factors that affect the social solidarity of rice farmers. This research uses the theory of social solidarity by Emile Durkheim. This research method uses a qualitative method. The results of the study show that the form of social solidarity of farmers is divided into two, namely mechanical solidarity and organic solidarity. Mechanical solidarity can be seen in the activities of mutual cooperation and khanduri blang. Meanwhile, organic solidarity can be seen in rice field land cultivation activities, rice planting, rice maintenance and rice harvesting. There are two factors that affect the social solidarity of rice farmers, namely inhibiting factors and supporting factors. The inhibiting factors are modernization and materialism. The supporting factors are traditions and religious values.